COMPRESSIVE THERAPY SIDE EFFECTS DURING THE TREATMENT OF VENOUS LEG ULCERS - Golubović, Maša; Binić, Iva (Acta medicae Medianae, 2025)
Venous ulceration arises as an end stage of chronic venous insufficiency. The application of an adequate level of compression therapy is the gold standard of treatment. The study to assess the frequency of complications from compression therapy used to treat venous ulcerations of the lower limbs, in relation to age and the level of compression applied. The study included 102 outpatients with venous ulceration treated at the Niš University Clinical Center’s Clinic of Dermatovenereology. Ulcers were monitored within 24 weeks from the start of treatment. There were two groups of patients, ≥ 65 years old and < 65 years old, divided into two subgroups in relation to the degree of compression therapy. The following were monitored: sex, age, body mass index, area, localization and number of ulcerations, degree of granulation tissue and fibrin in the ulceration, presence of dermatitis, lipodermatosclerosis, infection, and duration of the disease. It was found that there was a statistically significant difference in the number of previous ulceration episodes, the size of the ulcerations and the duration of the disease between the examined groups. Additionally, a difference was found in the level of pain in relation to the degree of compression, as well as the risk of paresthesia in relation to age. A higher degree of compression therapy in both age groups led to an increase in the rate of patients with paresthesia and a higher level of pain sensitivity. The study showed no statistically significant risk of superficial necrosis and skin discoloration related to the age of patients.